2003
DOI: 10.1002/anie.200351997
|View full text |Cite
|
Sign up to set email alerts
|

A Well‐Defined Complex for Palladium‐Catalyzed Aerobic Oxidation of Alcohols: Design, Synthesis, and Mechanistic Considerations

Abstract: A breath of fresh air: A variety of alcohols are oxidized using 0.5–0.1 mol % of the catalyst, and in some cases the oxidation can simply be carried out open to the air (see scheme). Mechanistic insight into the mechanism is provided by a crystal structure that shows remarkable hydrogen bonds between the coordinated water and acetate ligands and an unprecedented large kinetic isotope effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
108
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 299 publications
(112 citation statements)
references
References 23 publications
4
108
0
Order By: Relevance
“…Therefore, we performed some additional experiments to compare more directly the efficiency of the various catalysts. Determination of the conversion curves under our reaction conditions ( Figure 3) revealed that complex 1 was indeed the most efficient catalyst for this reaction, with an initial activity almost two times higher than that of both PdA C H T U N G T R E N N U N G (OAc) 2 and monocarbene palladium complex 2, [16] which expectedly forms Nolans bis(trifluoroacetate) complex in situ. After five hours of reaction, PdA C H T U N G T R E N N U N G (OAc) 2 gave only 37 % conversion with 92 % selectivity for the Z product, while complex 2 gave 31 % conversion with 94 % selectivity.…”
Section: Resultsmentioning
confidence: 85%
See 1 more Smart Citation
“…Therefore, we performed some additional experiments to compare more directly the efficiency of the various catalysts. Determination of the conversion curves under our reaction conditions ( Figure 3) revealed that complex 1 was indeed the most efficient catalyst for this reaction, with an initial activity almost two times higher than that of both PdA C H T U N G T R E N N U N G (OAc) 2 and monocarbene palladium complex 2, [16] which expectedly forms Nolans bis(trifluoroacetate) complex in situ. After five hours of reaction, PdA C H T U N G T R E N N U N G (OAc) 2 gave only 37 % conversion with 92 % selectivity for the Z product, while complex 2 gave 31 % conversion with 94 % selectivity.…”
Section: Resultsmentioning
confidence: 85%
“…The reagents were purchased by Aldrich as high-purity products and generally used as received. Complexes 2, [16] 4, [18] 5, [19] [b] In parentheses the yield in the hydrolysed product. Reaction conditions: see Experimental Section.…”
Section: Experimental Section General Remarksmentioning
confidence: 99%
“…These properties have led to a number of applications where NHC-based catalysts exhibit superior performance. Such NHC-metal complexes have been successfully utilized in cross-coupling reactions [16] and related processes, including hydrogenation [17], hydroformylation [18] hydrosilylation [19], oxidation [20], metathesis [21], cycloisomerisation of olefins [22], the synthesis of furans [23] and cyclopropanation reactions.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, variety of transition metal based catalysts (mainly cobalt, vanadium, ruthenium and palladium) has been intensively investigated for aerobic oxidation of alcohols so far. [77][78][79][80] Although metalloporphyrins have been used to catalyze the oxidation of alcohols with PhIO, t-BuOOH, KHSO 5 and m-CPBA (m-chloroperbenzoic acid) as oxidants, [81][82][83][84] few studies on metalloporphyrins-catalyzed oxidation of alcohols by molecular oxygen were reported. For examples, Woo and co-authors ever reported the aerobic homogeneous oxidation of benzyl alcohol with oxotitanium porphyrin (TTP)Ti=O (TTP=meso-tetra-p-tolylporphyrin), which gave benzaldehyde in modest yields (48%) after 94 hours in refluxing chlorobenzene.…”
Section: Oxidation Of Alcoholsmentioning
confidence: 99%